Tradisi Sedekah Bumi di Dusun Nanggulan: Perspektif Sosiologi Agama: The Tradition of Sedekah Bumi in Dusun Nanggulan: A Perspective from the Sociology of Religion - Permatasari, Shevia Putri; Fauzi, Agus Machfud (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2024)
Religion and tradition are two pivotal pillars in shaping the social views and behaviors within communities. In the context of Dusun Nanggulan's society, the practice of Sedekah Bumi serves as a distinctive example of how tradition interacts with religion to create social solidarity and preserve communal values. This study aims to deepen the understanding of the Sedekah Bumi practice in Dusun Nanggulan, particularly exploring how the community responds, maintains, and adapts this tradition in the context of evolving religious understandings. This article employs a qualitative approach, utilizing observation, interviews, and literature review for data collection. The findings of this study indicate that Sedekah Bumi remains highly relevant in the lives of the Dusun Nanggulan community. Despite changes in its execution, such as procedural adaptations and the participation of the younger generation, this practice continues to be a crucial means of expressing gratitude and strengthening social solidarity. The study concludes that the Sedekah Bumi practice in Dusun Nanggulan demonstrates how religion and tradition can collaborate to solidify a harmonious social structure within the community, while playing a vital role in preserving traditional values, facilitating intergenerational value transmission, and maintaining social cohesion in Dusun Nanggulan. Abstrak Agama dan tradisi merupakan dua pilar penting dalam membentuk pandangan dan perilaku sosial masyarakat. Dalam konteks masyarakat Dusun Nanggulan, praktik Sedekah Bumi menjadi contoh khas bagaimana tradisi berinteraksi dengan agama untuk menciptakan solidaritas sosial dan mempertahankan nilai-nilai komunal. Studi ini bertujuan untuk memperdalam pemahaman tentang praktik Sedekah Bumi di Dusun Nanggulan, khususnya dalam mengeksplorasi bagaimana masyarakat merespons, mempertahankan, dan mengadaptasi tradisi tersebut dalam konteks pemahaman agama yang berkembang. Artikel ini menggunakan pendekatan kualitatif dengan memanfaatkan observasi, wawancara, dan studi literatur untuk mengumpulkan data. Hasil kajian ini menunjukkan bahwa Sedekah Bumi masih sangat relevan dalam kehidupan masyarakat Dusun Nanggulan. Meskipun mengalami perubahan dalam pelaksanaan, seperti adaptasi prosesi dan partisipasi generasi muda, praktik ini tetap menjadi sarana penting untuk ekspresi syukur dan memperkuat solidaritas sosial. Kajian ini menyimpulkan bahwa praktik Sedekah Bumi di Dusun Nanggulan menunjukkan bahwa agama dan tradisi dapat bekerja sama untuk mengukuhkan struktur sosial yang serasi di dalam komunitas dan sekaligus memainkan peran penting dalam menjaga nilai-nilai tradisional, memfasilitasi transmisi nilai antargenerasi, serta memelihara kebersamaan sosial di Dusun Nanggulan.